Answer:
A) 4x - 2y + 3z = - 3
B) 2x - 3y + 2z = 1
C) 6x + 10z = -2
Multiply A) by -1.5
A) -6x +3y -4.5z = 4.5 Then adding to B)
B) 2x - 3y + 2z = 1
D) -4x -2.5z = 5.5 then we add this to C)
C) 6x + 10z = -2 Now we multiply D) by 1.5
D) -6x -3.75z = 8.25 Adding C) + D)
6.25z = 6.25
z = 1 Then putting z = 1 into A) and B)
A) 4x - 2y + 3 = - 3 equals A) 4x -2y = -6
B) 2x - 3y + 2 = 1 equals B) 2x -3y = -1 we divide A) by -2
A) -2x + y = 3 then adding to B
B) 2x - 3y = -1
-2y = 2
y = -1
FINALLY solving for x we'll use equation A)
A) 4x - 2*-1 + 3*1 = - 3
A) 4x +2 + 3 = -3
A) 4x = -8
x = -2
(Yes, it's just that easy. LOL)
Explanation: